Dampak Donasi Masyarakat Terhadap Aktivitas Terorisme di Indonesia (Studi Kasus Putusan Pengadilan Negeri Jakarta Barat Nomor 363/Pid.Sus/2022/PN Jkt.Brt) - Renaldi; Purba, Lilis (HUMANIORUM, 2025)
The terrorism movement in Indonesia is a collection of groups that spread radical ideologies through violence or systematic, planned, and intentional threats of violence aimed at changing the state ideology, namely Pancasila. Terrorism is also a crime committed with systematic, planned, and deliberate violence or threats of violence. Terrorism is an extraordinary crime that can destroy the sovereignty of a nation and state, so its prevention and eradication must be done in extraordinary ways. In Indonesia, many people donate, and the country itself has been recorded as the most charitable nation in the world for several consecutive years. Factors influencing Indonesia to become the most charitable country include religious teachings that encourage giving, a culture of mutual assistance (gotong royong), and zakat as a mandatory form of charity among Muslims. This study aims to analyze the impact of donations on terrorism activities in Indonesia, focusing on the case study of the West Jakarta District Court Decision Number 363/Pid.Sus/2022/PN Jkt.Brt. Using a qualitative approach, this research explores how donation mechanisms can become a source of funding for terrorist groups, as well as the factors that drive individuals or communities to make contributions. Data is collected through document analysis and observation, which are then processed to identify patterns and relationships between donations and terrorism activities. The results of the study show that there is a gap in public awareness regarding the risks associated with donations, as well as the importance of education to prevent funding for terrorism activities. This research is expected to provide recommendations for authorities and the public to improve understanding of the impact of donations and the steps to combat terrorism funding.